The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1254/jphs.fp0070224
|View full text |Cite
|
Sign up to set email alerts
|

The Herbal Medicine Tokishakuyakusan Increases Fetal Blood Glucose Concentrations and Growth Hormone Levels and Improves Intrauterine Growth Retardation Induced by Nω-Nitro-L-arginine Methyl Ester

Abstract: Abstract. N ω -Nitro-L-arginine methyl ester (L-NAME) induces a pre-eclampsia-like syndrome in pregnant rats. We have previously reported the anti-hypertensive effects of several Japanese traditional (Kampo) medicines in this model, and one of these, Tokishakuyakusan (TS), also improved intrauterine growth retardation (IUGR). In the present study, we characterized the effect of TS on IUGR. TS administration reversed the decrease in fetal body weight and fetal blood glucose concentration induced by the infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…At this time, blood glucose was lower in the right-sided fetuses (57 ± 8 mg/dL) than in maternal blood (102 ± 4). These right-sided fetal blood glucose levels would be considered hypoglycemic by postnatal standards but are considered euglycemic for late gestational fetal rats which typically have mean blood glucose levels near 50 mg/dL [ 31 34 ]. By contrast, left-sided fetuses had 128 ± 58% higher glucoses (131 ± 33 mg/dL) than right-sided fetuses ( Figure 1(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…At this time, blood glucose was lower in the right-sided fetuses (57 ± 8 mg/dL) than in maternal blood (102 ± 4). These right-sided fetal blood glucose levels would be considered hypoglycemic by postnatal standards but are considered euglycemic for late gestational fetal rats which typically have mean blood glucose levels near 50 mg/dL [ 31 34 ]. By contrast, left-sided fetuses had 128 ± 58% higher glucoses (131 ± 33 mg/dL) than right-sided fetuses ( Figure 1(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…But the increase in blood pressure secondary to L-NAME has been previously established. [42][43][44] Boluses of sildenafil were previously shown to decrease blood pressure and increase the heart rate in both normal and IUGR pregnancies, probably secondary to further vasodilation of the already dilated vascular beds. 24 Another limitation is the small sample size of the offspring in each group, which prohibited the use of more appropriate statistical tests for analyzing the effects in the fetuses considering the dams as the experimental unit.…”
Section: Discussionmentioning
confidence: 98%
“…The term ‘animal model of preeclampsia’ is commonly and consistently used when nitric oxide synthase inhibitor NG-nitro-L-arginine methylester (L-NAME) was administered from d14 of gestation to induce preeclampsia-like syndrome in rats [40] – [45] . It has been reported that although chronic treatment with L-NAME may not reproduce the entire disease entity, it produces virtually all the pathophysiologies of preeclampsia in the animal model [46] . In view of this the L-NAME induced rat model of pregnancy induced hypertension was used.…”
Section: Methodsmentioning
confidence: 99%